A Semi‐Empirical Approach for Tsunami Inundation: An Application to the Coasts of South Italy. Issue 11 (8th June 2022) - Melito, Lorenzo; Lalli, Francesco; Postacchini, Matteo; Brocchini, Maurizio
Abstract: Tsunamis in the Mediterranean Sea have been increasingly investigated recently due to past destructive events. We present a novel operational approach for evaluating tsunami‐induced inundation, based on a generalization of Green's law and a chain of intermediate and small‐scale simulations. At the intermediate level, simulations with a linear solver are made to identify the distribution of a novel parameter, namely α, condensing all nearshore wave transformations other than shoaling. α represents a proxy for coastal susceptibility to the tsunami impact. Small‐scale modeling of coastal flooding performed at locations for which a DTM is freely available, at the Esaro river estuary (Calabria) and in Bari (Apulia), yields inundation levels that compare well with those obtained via intermediate‐scale modeling, with a saving in computational time of about 41%. This demonstrates the value of α to "scale" the offshore wave input and reduce computational effort to evaluate flooding at regional scale. Plain Language Summary: An interest in studying the consequences of tsunamis has arisen also for the Mediterranean Sea in the last decades. In this manuscript we present a method for the evaluation of potential coastal inundation caused by the impact of tsunamis. The method exploits a chain of numerical simulations of wave propagation to move the tsunami from the source region down to the investigated coasts. The inundation estimate makes use of a simple parameter, named α, devised to encapsule all the transformation processes the tsunami undergoes in its travel from intermediate waters to the coastline. We apply the method to portions of the southern Italian coast with a prototype tsunami event, and we see that inundation levels achieved with faster, small‐scale simulations compare well with those obtained with longer, intermediate‐scale simulations. The method can be helpful as an implementation in recent tsunami warning systems developed to warn coastal communities on impending threats. Key Points: A modeling chain approach for the evaluation of tsunami inundation is described and applied to the coasts of South Italy The method exploits a semi‐empirical extension of the classical Green's law to general bathymetries, and dedicated numerical simulations The method allows for transposing computational effort from intermediate to shallow waters